Screening of heat stress-regulating active fractions in mung beans - Feng, Yuchao; Fan, Xia; Suo, Dengcheng; Zhang, Shu; Ma, Yantao; Wang, Haoyu; Guan, Xin; Yang, Hongzhi; Wang, Changyuan (Frontiers in Nutrition, 2023)
Heat stress caused by high temperature has important adverse effects on the safety and health status of humans and animals, whereby effective prevention is necessary in everyday life. A safer and more effective dietary intervention in the food industry to alleviate heat stress is highly feasible. This study was conducted on mung beans, a traditional food known for relieving summer heat, comprising polyphenols, proteins, peptides, polysaccharides, and oils as the main investigated components. Fifteen polyphenols were identified as the target monomer components based on non-targeted analysis on the ultraperformance liquid chromatography coupled with high-field quadrupole orbitrap high-resolution mass spectrometry (UHPLC-QE-HF-HRMS) platform and existing reports. Primary screening of all target fractions was performed using DPPH and ABTS free-radical scavenging assays. The results showed that the antioxidant activity of mung bean polyphenols (crude extract) and monomeric polyphenols was good, followed by that of oil and mung bean peptides, while the antioxidant activities of proteins and polysaccharides were relatively poor. A qualitative and quantitative assay for 20 polyphenols (15 polyphenols and five isomers) was then established based on platform-targeted analysis. Based on the content level, vitexin, orientin and caffeic acid were finally identified as monomeric polyphenolics of heat stress control in mung bean. Mild (39 °C), moderate (41 °C), and severe (43 °C) heat stress models were then successfully constructed based on mouse intestinal epithelial mode-k cells and human colorectal adenocarcinoma Caco-2 cell lines, with the best modelled heat stress time for both cells being 6 h. Screening of individual mung bean fractions was conducted using HSP70 mRNA content, a key indicator of the heat stress signature. The results showed that mung bean polyphenols (crude extract), vitexin, orientin and caffeic acid showed good heat stress regulatory effects at different levels of heat stress; the higher the level of heat stress, the more significant the regulatory effect, with orientin having the best effect. Polyphenols are the main heat stress-regulating components in mung beans, and the three monomeric polyphenols mentioned above may be the main heat stress-regulating substances in mung beans.